Insecticidal activity of a Melinis minutiflora grass extract on Stomoxys calcitrans flies - Tobón, Flor A (Revista Colombiana de Ciencias Pecuarias, 2011)
Several extraction methods were utilized to study the insecticidal activity of a Melinis minutiflora grass extract. Four concentrations (10, 20, 40, 80%) of the product which had the highest yield (i.e., a wax-free hexane extract) were tested to establish its insecticidal activity on S. calcitrans flies (adults and larvae). It is hypothesized that an 80% plant extract has a lethal effect similar to or higher than cypermethrin on flies and larvae. Mortality rates were assessed by survival analysis comparing the Kaplan-Meier mortality curves against the standard pyrethroid (cypermethrin) or against the solvent (ethyl acetate). The median mortality (time to kill 50% of the population) of adult flies exposed to cypermethrin over an eight-hour period was one hour, while it was three hours for the highest concentration of the extract tested. Both medians were significantly lower than those of the other treatments. The median mortality of larvae exposed to cypermethrin for a 30 minute period was four minutes, while it was eight minutes for the highest concentration (80%) of the plant extract. These values were significantly lower than the medians obtained for the other concentrations of the extract. These data suggest that extracts obtained from Melinis minutiflora grass could be a safe substitute for chemical insecticides. Key words: insecticidal activity, Melinis minutiflora, Stomoxys calcitrans. Resumen Después de evaluar tres métodos para obtener un extracto del pasto Melinis minutiflora, cuatro concentraciones (10, 20, 40, 80%) del producto que tuvo el mayor rendimiento –un extracto hexanoico libre de ceras– fueron comparadas para establecer su actividad insecticida sobre moscas Stomoxys calcitrans (adultos y larvas). Se plantea como hipótesis de investigación, que una concentración de 80% del extracto, tiene un efecto letal similar o superior al de la cipermetrina. Las tasas de mortalidad se evaluaron mediante análisis de supervivencia comparando las curvas de mortalidad de Kaplan-Meier para un piretroide (cipermetrina) y el solvente (acetato de etilo). La mediana de la mortalidad (o sea el tiempo requerido para matar el 50% de la población) de las moscas adultas expuestas a cipermetrina durante un período de ocho horas fue de una hora, mientras que fue de tres horas para el extracto al 80%. Ambas medianas fueron significativamente menores que las de los otros tratamientos. La mediana de la mortalidad de larvas expuestas a cipermetrina para un período de 30 minutos fue de cuatro minutos y de ocho minutos para la concentración más alta (80%) del extracto del pasto. Estos valores fueron significativamente menores que las medianas obtenidas para las otras concentraciones del extracto. Palabras clave: acción insecticida, Melinis minutiflora, Stomoxys calcitrans. Resumo Neste trabalho foram testados vários métodos de extração química para obter diferentes extratos do pasto Melinis minutiflora para estabelecer com qual obtém-se maior quantidade e maior atividade inseticida. O extrato obtido em maior quantidade foi o extrato hexânico livre de ceras em 0.60%, o qual determinou-se sua ação inseticida sobre larvas e adultos de S. calcitrans reproduzidas no laboratório. A mortalidade que produzem quatro concentrações (10, 20, 40, 80%) do extrato livre de ceras, percebe-se mediante a análise estatística de sobrevivência comparando as curvas de mortalidade de Kaplan-Meier frente ao padrão de referencia mosquicida cipermetrina (piretroide), e solvente acetato de etilo. As análise estatística da atividade inseticida das concentrações do extrato sobre S. calcitrans adultos em um período de oito horas, expressa pela mediana (tempo no qual se morrem o 50% da população), do efeito inseticida da cipermetrina foi de 1 hora, por enquanto na mediana do efeito inseticida do extrato à concentração de 80% sobre moscas adultas foi de 3.0 horas. Ambas as médias foram significativamente inferiores quando comparados com os dos demais tratamentos. Quanto à atividade inseticida de mortalidade, 50% das larvas expostas à cipermetrina ou acetato de etila por um prazo de 30 minutos a 4 minutos e a eficácia inseticida do extrato a 80% das larvas foi de 8 minutos, valores significativamente inferior ao de outras concentrações.